DIVERSITY AND GLOBAL COMMUNICATION - Iskandarova Kamola Ulugbek kizi (European Science Publishing, 2024)
Language diversity is fundamental to human civilization, reflecting the rich array of cultures and histories worldwide. In today's interconnected world, where global communication is vital, the dynamics of language diversity are pivotal. This article explores the importance of language diversity in global communication, examining its impact on cultural exchange, identity preservation, and the challenges and opportunities presented by linguistic globalization.
Keywords: Language diversity, global communication, cultural exchange, linguistic globalization, identity preservation, multilingualism, language policy.